Niclosamide does not modulate airway epithelial function through blocking of the calcium activated chloride channel, TMEM16A - Danahay, Henry; Lilley, Sarah; Adley, Kathryn; Charlton, Holly; Fox, Roy; Gosling, Martin (Frontiers in Pharmacology, 2023)
Niclosamide and benzbromarone have been described as inhibitors of the calcium activated chloride channel, TMEM16A, and on this basis have been considered and tested as clinical candidates for the treatment of airway diseases. However, both compounds have previously demonstrated activity on a range of additional biological targets and it is unclear from the literature to what extent any activity on TMEM16A may contribute to efficacy in these models of airway disease. The aim of the present study was therefore to examine the pharmacology and selectivity of these clinical candidates together with a structurally unrelated TMEM16A blocker, Ani9, in a range of functional assays to better appreciate the putative role of TMEM16A in the regulation of both epithelial ion transport and the development of an airway epithelial mucus secretory phenoptype. Benzbromarone and Ani9 both attenuated recombinant TMEM16A activity in patch clamp studies, whereas in contrast, niclosamide induced a paradoxical potentiation of the TMEM16A-mediated current. Niclosamide and benzbromarone were also demonstrated to attenuate receptor-dependent increases in intracellular Ca2+ levels ([Ca2+]i) which likely contributed to their concomitant attenuation of the Ca2+-stimulated short-circuit current responses of FRT-TMEM16A and primary human bronchial epithelial (HBE) cells. In contrast, Ani9 attenuated the Ca2+-stimulated short-circuit current responses of both cell systems without influencing [Ca2+]i which supports a true channel blocking mechanism for this compound. Additional studies using HBE cells revealed effects of both niclosamide and benzbromarone on global ion transport processes (absorptive and secretory) as well as signs of toxicity (elevated LDH levels, loss of transepithelial resistance) that were not shared by Ani9. Ani9 also failed to influence the IL-13 induced differentiation of HBE towards a goblet cell rich, mucus hypersecreting epithelium, whereas niclosamide and benzbromarone attenuated numbers of both goblet and multiciliated cells, that would be consistent with cellular toxicity. Together these data challenge the description of niclosamide as a TMEM16A blocker and illustrate a range of off-target effects of both niclosamide and benzbromarone which may contribute to the reported activity in models of airway function.